2014
DOI: 10.1051/0004-6361/201423644
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength characterization of faint ultra steep spectrum radio sources: A search for high-redshift radio galaxies

Abstract: Context. Ultra steep spectrum (USS) radio sources are one of the efficient tracers of powerful high-z radio galaxies (HzRGs). In contrast to searches for powerful HzRGs from radio surveys of moderate depths, fainter USS samples derived from deeper radio surveys can be useful in finding HzRGs at even higher redshifts and in unveiling a population of obscured weaker radio-loud AGN at moderate redshifts. Aims. Using our 325 MHz GMRT observations (5σ ∼ 800 μJy) and 1.4 GHz VLA observations (5σ ∼ 80−100 μJy) availa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 126 publications
(258 reference statements)
0
26
0
Order By: Relevance
“…Studies have shown USS are good candidates for high redshift radio galaxies (Riseley et al 2016) which are among the most luminous and massive galaxies (e.g. De Breuck & Reuland 2005;Bornancini et al 2007;Singh et al 2014) and are believed to be progenitors of the massive elliptical galaxies in the local Universe. Their extremely steep spectrum is generally attributed to radiation losses of relativistic electrons in the radio lobes, meaning they are most luminous at lower radio frequencies (Mahony et al 2016).…”
Section: Ultra Steep Spectrum Sourcesmentioning
confidence: 99%
“…Studies have shown USS are good candidates for high redshift radio galaxies (Riseley et al 2016) which are among the most luminous and massive galaxies (e.g. De Breuck & Reuland 2005;Bornancini et al 2007;Singh et al 2014) and are believed to be progenitors of the massive elliptical galaxies in the local Universe. Their extremely steep spectrum is generally attributed to radiation losses of relativistic electrons in the radio lobes, meaning they are most luminous at lower radio frequencies (Mahony et al 2016).…”
Section: Ultra Steep Spectrum Sourcesmentioning
confidence: 99%
“…Moreover, the extremely high radio-to-IR flux density ratios of IFRS overlap with those of this HzRG sample. Recently, Singh et al (2014) searched for HzRGs in faint ultra steep spectrum (USS) radio sources and found several sources overlapping with the selection criteria of IFRS.…”
Section: Middelbergmentioning
confidence: 99%
“…A successful method of identification of HzRGs from allsky radio surveys is to first create samples of radio sources that display an ultra-steep spectral index (α, where S ∝ ν α ) and then follow these up at optical and infrared wavelengths (Tielens et al 1979;Röttgering et al 1994;Chambers et al 1996;Blundell et al 1999;De Breuck et al 2000a;Ishwara-Chandra et al 2010;Afonso et al 2011;Singh et al 2014). This method is effective owing to the apparent correlation that exists between the redshift of a radio source and the steepness of its low-frequency radio spectrum (see Ker et al 2012, for example).…”
Section: Introductionmentioning
confidence: 99%